2010
DOI: 10.3945/jn.110.127647
|View full text |Cite
|
Sign up to set email alerts
|

Excess Leucine Intake Enhances Muscle Anabolic Signaling but Not Net Protein Anabolism in Young Men and Women

Abstract: Essential amino acids (EAA) stimulate skeletal muscle protein synthesis (MPS) in humans. Leucine may have a greater stimulatory effect on MPS than other EAA and/or decrease muscle protein breakdown (MPB). To determine the effect of 2 different leucine concentrations on muscle protein turnover and associated signaling, young men (n = 6) and women (n = 8) ingested 10 g EAA in 1 of 2 groups: composition typical of high quality proteins (CTRL; 1.8 g leucine) or increased leucine concentration (LEU; 3.5 g leucine).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
171
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(202 citation statements)
references
References 55 publications
14
171
5
2
Order By: Relevance
“…When leucine-enriched supplements have been given to young subjects in connection with resistance exercise, little or no additional effect on protein synthesis or protein balance occurred (Katsanos et al 2006;Koopman et al 2005;Tipton et al 2009;Glynn et al 2010b). This lack of effect may, however, simply be due to the fact that the unenriched supplement itself already contains sufficient leucine to stimulate protein synthesis maximally.…”
mentioning
confidence: 95%
“…When leucine-enriched supplements have been given to young subjects in connection with resistance exercise, little or no additional effect on protein synthesis or protein balance occurred (Katsanos et al 2006;Koopman et al 2005;Tipton et al 2009;Glynn et al 2010b). This lack of effect may, however, simply be due to the fact that the unenriched supplement itself already contains sufficient leucine to stimulate protein synthesis maximally.…”
mentioning
confidence: 95%
“…It has been reported that leucine deprivation in myoblast and myotubes increased (78) and leucine administration in cell culture (44,66), rats (87,88), and humans (29,41) decreased the phosphorylation of eEF2, a key component of the elongation process. In the current study, phosphorylation of eEF2 did not differ between the CON ϩ LEU and the CON ϩ ALA groups.…”
Section: E708 Leucine Pulses Increase Lean Gain In Neonatesmentioning
confidence: 99%
“…However, ingesting larger quantities of amino acids (e.g., 25-30 g) effectively stimulates muscle protein synthesis in both young and older individuals (55,56). Notably, the responsiveness of muscle protein synthesis in the elderly to small quantities of essential amino acids can be overcome by increasing the leucine content of the mixture (21,32). Similar results have been reported for studies in rats in which the age-related resistance of skeletal muscle protein synthesis to stimulation by a protein diet can be overcome by supplementation with leucine (14).…”
mentioning
confidence: 99%